High-Precision X-Ray Measurements 2023 - Fabrizio Napolitano; Alessandro Scordo (Condensed Matter)
High-Precision X-ray Measurements 2023 is a Special Issue of the journal Condensed Matter enclosing the scientific content of the 2023 High-Precision X-ray Measurements (HPXRM) conference [...]